2012
DOI: 10.1111/j.1464-410x.2011.10865.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical simulators in urological training – views of UK Training Programme Directors

Abstract: What's known on the subject? and What does the study add? The role of surgical simulators is currently being debated in urological and other surgical specialties. Simulators are not presently implemented in the UK urology training curriculum. The availability of simulators and the opinions of Training Programme Directors' (TPD) on their role have not been described. In the present questionnaire‐based survey, the trainees of most, but not all, UK TPDs had access to laparoscopic simulators, and that all respondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…4,17 Laparoscopic and endoscopic surgical simulators are already well established for general surgical resident training. [23][24][25][26] In a review of these simulators, Carter et al 27 concluded that for surgical simulators to be effective, they must follow the basic principles of assessment that include alignment with the learning content, validity, and reliability. In other words, instruction of a particular surgical task on a simulator must result in acquiring the skills to perform the same procedural task in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…4,17 Laparoscopic and endoscopic surgical simulators are already well established for general surgical resident training. [23][24][25][26] In a review of these simulators, Carter et al 27 concluded that for surgical simulators to be effective, they must follow the basic principles of assessment that include alignment with the learning content, validity, and reliability. In other words, instruction of a particular surgical task on a simulator must result in acquiring the skills to perform the same procedural task in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…The overall realism was median 8 on the 10-point scale (range 6-9). The simulator was judged to be most useful in learning eye-hand coordination (score 8 [6][7][8][9][10]) and least useful in learning to avoid complications (score 6.5 [3][4][5][6][7][8][9]). All aspects of the simulator were rated above the acceptability threshold of 6 of 10, 20 clearly demonstrating face validity and content validity of this simulator.…”
Section: Training Needs Analysismentioning
confidence: 99%
“…6 Simulation training is increasingly used in addition to the classical master-apprentice type of training to provide a safe and controlled environment for learning and preserving skills. 7 Skills training on simulators can reduce the clinical training time by effectively advancing residents through their early learning curve. 8,9 Ideally, simulation-based skills training should be incorporated into urological curricula, requiring residents to reach minimum proficiency on a simulator before being allowed to undertake surgical procedures in a supervised clinical setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simülasyon eğitiminin cerrahi pratikteki performası artırdığına yönelik çok sayıda çalışma bulunmaktadır (3). İngiltere'de 'SIMULATE' adlı pratik eğitim bazlı ulusal simülasyon programı geliştirilmiş ve online olarak bu sistem cerrahi pratikte kullanılmaktadır (4)(5)(6).…”
unclassified